2010
DOI: 10.1089/thy.2009.0332
|View full text |Cite
|
Sign up to set email alerts
|

Oncofetal Fibronectin mRNA Is Highly Abundant in the Blood of Patients with Papillary Thyroid Carcinoma and Correlates with High-Serum Thyroid-Stimulating Hormone Levels

Abstract: onfFN transcripts are highly abundant in the peripheral blood of patients with PTC. L-T4 withdrawal, which produced elevated serum TSH concentrations in these athyroidic patients, markedly increased the fraction with positive tests for serum onfFN mRNA at all stages of the disease. Analyzing onfFN mRNA in the absence of a TSH stimulus allows a much better discrimination of different states of PTC disease and, based on current concepts of the significance of circulating mRNA, may be a useful tool to detect circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…Our observations were indeed similar to the subsequent work by the same group (Wehmeier et al, 2010) 27 in that for the disease-free group, the onfFN expression range was wide and the maximum value was higher than the metastatic groups. Their explanation was that their disease-free patients were perhaps in fact harboring disease that was not detected by their follow-up scheme and that the onfFN mRNA was very sensitive for disease detection.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our observations were indeed similar to the subsequent work by the same group (Wehmeier et al, 2010) 27 in that for the disease-free group, the onfFN expression range was wide and the maximum value was higher than the metastatic groups. Their explanation was that their disease-free patients were perhaps in fact harboring disease that was not detected by their follow-up scheme and that the onfFN mRNA was very sensitive for disease detection.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, our metastatic groups were those who had imaging evidence on either 131 I total body scan or computed tomography in addition of having the serum Tg level of > 2 ng/ml. Even with a loose criterion of metastasis, the metastatic group of constituted only 8% of the patients in the study of Wehmeier et al (2010); while in ours the combined metastatic groups constituted 41%, or the group with distant metastasis alone 27%.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The authors suggested that onfFN mRNA analysis may be a specific tool for monitoring micrometastases in the context of minimal residual disease or for assessing tumor response to therapy. Continuing their studies they performed the analysis of mRNA level in peripheral blood of PTC patients who were previously treated by thyreoidectomy and treated by levothyroxine to determine if onfFN levels are correlated with the status of the disease or with thyroid-stimulating hormone (TSH) serum concentrations (Wehmeier et al 2010). The mean value of onfFN mRNA in bloods from healthy subjects was used as control.…”
Section: Fibronectinmentioning
confidence: 99%